Diseño, planeación e implementación de dispositivo médico para la cuantificación de presión en tratamiento de presoterapia : Biopressure (2020)
An impacting medical problem was identified through an observation process integrating literature review, interviews with treating physicians and experts in design of compressive elements used for the treatment of pressotherapy in burn survivors. Considering the information collected, with active feedback from personnel in the health area, a specific need was recognized and formalized, focused on the lack of ways to quantify the pressure applied by compression elements on burns, which results in a lack of knowledge and, therefore, mismanagement in the application of treatment, causing lack of adherence and intermittence of the patient. To address the problem, a medical device was designed that presents a simple, easy to implement and economically accessible solution, which can be of help to health personnel and stakeholders involved in the design and implementation of pressotherapy garments. To evaluate the potential of the device, a business model was developed defining potential investors, allies, and users, as well as characters, resources and key regulatory requirements for the development and implementation of the device. BioPressure, our solution proposal is a device with potential within the health market, considering that there are no similar devices that perform the same task, the size, and characteristics of the pressotherapy market and the operation plan designed for a term of 5 years of execution.--Taken from the Degree Document Format.